THE STRUGGLE OF VICTORIAN WOM EN IN NOVEL “LITTLE WOMEN” BY LOUISA MAY ALCOTT - Cinda Amilia Rahman (Universitas Muhammadiyah Gorontalo, 2018)
This research discusses Louisa May Alcott’s novel, “Little Women”. It is a story about four sisters and mother in the March Family. The novel, which has a background in the Victorian Era, addresses many issues about women. The description of women at that time, positions in the Family, Education and Public work environment. Therefore this study aims to determine aspects of the struggle of women in Victorian era in terms of family, education, and Public work environment using a gynocriticism approach. The data used documentation data where data comes from novels and other supporting sources. The results of this study researchers found that there were aspects of women’s struggle at that time in the novel “Little Women” in Family, Education and Public work environment. In addition, researcher found a relation between the life story of author Louisa May Alcott and the “Little Women” novel that has been presented in some data.Keywords: Victorian Era, Gynocriticism, Louisa May Alcott, Little Women.